Balancing constituency and congruence: How constituency involvement affects positional congruence between organized interests and the general public. Issue 1 (26th December 2019) - Willems, Evelien; De Bruycker, Iskander
Abstract: This article asks to what extent and under which conditions interest groups are congruent with public opinion. We argue that interest groups can be caught in a balancing act between engaging with their constituency on the one hand and aligning their position with the broader public on the other hand. We contribute to previous studies by arguing that the effect of interest group type on congruence is moderated by the degree to which constituencies are involved in advocacy processes and the salience of policy issues. We test these expectations by analyzing 314 media claims made by Belgian interest groups regarding 58 policy issues. The results demonstrate that citizen groups with formal members are more prone to share the position of the broader public compared to concentrated interest groups such as business associations, especially if they involve their members in advocacy activities and when issues are salient in the media.